Construction and Identification of Eukaryotic Expression Vector pEGFP-N1-MIC-1 for Mouse MIC-1 Gene and Its Effect on Gastric Cancer Cells - HuiPeng Zhang; Zhongyu Qin; ShuaiShuai Shi; YunFei Li; Yang Song; YiQiang Zhang (Analytical Cellular Pathology)
This study aimed to construct an eukaryotic expression vector, pEGFP-N1-MIC-1, for overexpressing the mouse macrophage inhibitory cytokine-1 (MIC-1) gene. Additionally, we transfected the MFC cell line to observe the upregulation of MIC-1 gene expression and assess its impact on macrophage phenotype conversion. Enzyme digestion and DNA sequencing confirmed the successful construction of the pEGFP-N1-MIC-1 vector. The transfected MFC cells exhibited a significant increase in MIC-1 protein expression levels. Furthermore, transfection with pEGFP-N1-MIC-1 increased the migration and colony formation capabilities of MFC cells. These results may contribute to future research and the development of therapeutic interventions targeting MIC-1 in macrophages, particularly in the context of gastric cancer.